Transnational cooperation: An explorative collection - Sven Grimm; Stephan Klingebiel (German Institute of Development and Sustainability (IDOS), 2024)
The present collection of short papers is an experimental, explorative and introspective German Institute of Development and Sustainability (IDOS) project on international and transnational cooperation for development and sustainability. It is the product of internal brainstorming discussions at IDOS in mid-2022 that aspired to conduct a preliminary, exemplary mapping of the use of 'transnational lenses' and their understandings across various work strands at the institute. This might lead to new questions in our work, or it might simply be an attempt to look at our topics of interest with a different perspective.
Keywords: 320; transnational cooperation; development; development cooperation; training; knowledge cooperation; non-state actors